2020
DOI: 10.3390/ijms21134759
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways That Control Muscle Mass

Abstract: The loss of skeletal muscle mass under a wide range of acute and chronic maladies is associated with poor prognosis, reduced quality of life, and increased mortality. Decades of research indicate the importance of skeletal muscle for whole body metabolism, glucose homeostasis, as well as overall health and wellbeing. This tissue’s remarkable ability to rapidly and effectively adapt to changing environmental cues is a double-edged sword. Physiological adaptations that are beneficial throughout life beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 206 publications
(299 reference statements)
0
88
2
2
Order By: Relevance
“…The NF-kB signaling pathway is activated upon inflammatory cytokine production and the MuRF1 promoter possesses NF-kB binding sites ( Figure 2 b), which enables a direct induction of MuRF1 mRNA production [ 67 ] ( Figure 2 a). The NF-kB pathway can be activated by TNFα or by TWEAK, two inflammatory cytokines that potently induce MuRF1 overexpression and muscle atrophy [ 68 , 69 ]. As an example of the respective roles of the different transcription factors, the NF-kB sites were required for disuse atrophy-linked MuRF1 expression, while FoxO sites were dispensable [ 67 ].…”
Section: Regulation Of Murf1mentioning
confidence: 99%
“…The NF-kB signaling pathway is activated upon inflammatory cytokine production and the MuRF1 promoter possesses NF-kB binding sites ( Figure 2 b), which enables a direct induction of MuRF1 mRNA production [ 67 ] ( Figure 2 a). The NF-kB pathway can be activated by TNFα or by TWEAK, two inflammatory cytokines that potently induce MuRF1 overexpression and muscle atrophy [ 68 , 69 ]. As an example of the respective roles of the different transcription factors, the NF-kB sites were required for disuse atrophy-linked MuRF1 expression, while FoxO sites were dispensable [ 67 ].…”
Section: Regulation Of Murf1mentioning
confidence: 99%
“…Experimental models reproducing different conditions leading to muscle atrophy have been developed and used to identify master regulators of atrophy by means of either pharmacological or genetic tools. Detailed reviews about the involvement of regulators of muscle transcription, protein synthesis, and anabolic signaling pathways, protein catabolism and autophagy have recently appeared [ 19 , 20 , 21 , 22 ]. Therefore, we would largely refer to these contributions and limit our presentation to knowledge concerning evidence of the major or partial involvement of these regulators with costamere components in different atrophy conditions.…”
Section: Master Regulators Of Muscle Atrophymentioning
confidence: 99%
“…FoxOs (FoxO1, FoxO3, FoxO4) are involved in most types of muscle atrophy, since the inhibition or genetic deletion of multiple FoxOs completely prevented its development induced by fasting, glucocorticoid treatment and diabetes [ 19 ]. Conversely, deletion of all FoxO family members only attenuated muscle atrophy induced by limb immobilization and reduced, but not abolished, the expression of major atrogenes, such as MuRF1 and MAFbx/Atrogin-1 [ 23 ].…”
Section: Master Regulators Of Muscle Atrophymentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous reports, high potassium levels depolarizes smooth muscle cells that opens up voltage gated calcium channels resulting in entry of calcium ions inside the cells thereby leading to activation of smooth muscle contraction [44] The role of potassium in muscle contraction shown in Figure 2b. It had reported that activation of mTORC1 signalling correlated with decline in muscle mass [45,46] activated mTORC1induces oxidative stress that leads to protein degradation, autophagy and necrosis showing an aged phenotype [47]. The signalling pathway connecting potassium deficiency and ageing shown in…”
Section: Potassium (K)mentioning
confidence: 99%